Study of occult stress urinary incontinence in pelvic organ prolapse - Reddy, Nemakallu Sarala; Ghose, Seetesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pelvic organ prolapse and stress urinary incontinence are two common health-related conditions. If a woman with pelvic organ prolapse leaks only when the prolapse is reduced, it is called occult stress urinary incontinence (OSUI). The prevalence of OSUI in women with severe genitourinary prolapse varies from 27-68% in literature. In this study we want to find out the relationship between OSUI and stress urinary incontinence (SUI) following corrective surgery.The objectives of the study are to determine the number of women with urinary leak following reduction of prolapse before surgery; to determine the number women with occult stress urinary incontinence developing stress urinary incontinence following surgery and to determine the risk of developing stress urinary incontinence after vaginal hysterectomy and pelvic floor repair in these women. Methods: This is a longitudinal observational study. All women with pelvic organ prolapse (POP) of grade II or higher requiring corrective surgery were initially evaluated for OSUI using vaginal pack and followed up post operatively at 6 weeks and 12 weeks using QUID to look for post-operative stress urinary incontinence (POSUI). Results: The overall incidence of OSUI in our study was 7.5%. OSUI was significantly associated with factors like older age, higher BMI, high parity, short inter pregnancy interval and higher grade of prolapse and not significantly associated with factors like place of delivery, delivery events and mode of delivery. Conclusions: It is important to test all women with POP for OSUI and patients with OSUI need long term follow up to detect POSUI